Care for the Elderly in the Indigenous Peoples of the Lampung Pepadun Tribe: Islamic Law Perspective - Napsiah - Napsiah (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2019)
Abstract: The objective of this research was to find out the caring of elderly Lampung that carried out by the family, particularly by the son or eldest son of the family. This research based on two cases of aged Lampung individuals, by using observation as well as interview, and secondary data as sources of research. The research finding is that the Lampung elderly, whether they live under the same roof with the married son (or eldest son) or not, are the responsibility of that son because it is disseminated among the Lampung people from early childhood. The son is regarded as replacement of the parent, and this understanding has implemented through common law. Meanwhile, the religion obliges the boys to responsible for the family. Therefore, no matter how complete the nursing home facilities are facilitated by the government, the elderly still supported by their own biological children.Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengasuhan lansia Lampung yang dilakukan oleh keluarga khususnya oleh putra atau putra sulung keluarga. Penelitian ini didasarkan pada dua kasus lansia  Lampung, dengan menggunakan observasi, wawancara dan data sekunder sebagai sumber penelitian. Hasil penelitian menunjukkan bahwa lansia Lampung yang tinggal serumah dengan anak yang sudah menikah atau tidak tinggal serumah dengan anak laki-laki, menjadi tanggung jawab anak laki-laki tersebut. Anak laki-laki dianggap sebagai pengganti orang tua, dan pemahaman ini diterapkan melalui hukum adat. Selain itu, agama mewajibkan anak laki-laki untuk bertanggung jawab terhadap keluarga. Oleh karena itu, selengkap apapun fasilitas panti jompo yang difasilitasi oleh pemerintah, para lansia tetap disantuni oleh anak kandungnya sendiri.